Simulation of autonomous systems in the extended marine domain. (2016) - Tremori, Alberto; Agresta, Matteo; Ferrando, Angelo
This paper is focused on characteristics and goals of an integrated architecture which aims at reproducing joint interoperability among autonomous systems. The paper proposes an experimentation over a scenario developed for the maritime context that uses an innovative simulator. The authors' goal, during such research, consists of identifying requirements related to these simulators so that they accurately keep into account the most important elements affecting real operative context. This analysis is addressing training (Kennedy, 2010), engineering and it could be further developed for supporting or operation supervision. General architecture devoted to integrate such simulators within a federation, together with the approach that has been used in order to carry out this operation, represent the subjects of this paper; the mission environment has been created with the only goal to test the federation, and similarly simulation architecture and conceptual models are validated through proposed preliminary activities.